Challenges of Kidney transplantation: Cadaver Donor - Bhuiyan, AKM Zamanul Islam (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.42-43